Editorial: Precision vaccinology for infectious diseases - Mahbuba Rahman (198499) (2024)
In the ever-evolving landscape of infectious diseases, the quest for effective preventive measures has reached a pivotal stage. The rise of precision vaccinology signifies a groundbreaking shift in vaccination strategies, offering bespoke solutions that acknowledge the diversity of individual immune responses. This Research Topic of Frontiers in Immunology explored precision vaccinology, where distinct immunity in diverse vulnerable populations dynamic interplay of genes, proteins, and metabolites within the human body is leveraged to craft precise and potent vaccines against infectious pathogens. International researchers have joined forces to collaboratively advance precision vaccinology. Through original research, comprehensive reviews, and meticulously curated datasets, these esteemed experts shed light on the current challenges and opportunities in vaccine discovery and development, guiding the way towards immunization approaches tailored to meet the specific requirements of particular groups. Other Information Published in: Frontiers in Immunology License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3389/fimmu.2024.1400443